Penerapan Project Based Learning dengan Media Video dan PowerPoint untuk Meningkatkan Hasil Belajar Siswa Kelas V - Suci Rahmadani; Hamna; Mustakim; Ikbal Ikbal (Tolis Ilmiah : Jurnal Penelitian, 2026)
This research aims to improve student learning outcomes by implementing a project-based learning model in thematic learning in class V at SDN 10 Tolitoli. Apart from that, this research also aims to analyze how the project-based learning model is implemented and to measure how good student learning outcomes are after participating in learning using this model. This research is classroom action research which is carried out in 2 cycles, each cycle consisting of 3 stages, observation, planning and action. Based on the results obtained, it shows that there is an increase from the first cycle to the second cycle. In cycle 1 there were 7 students with a percentage of 18.42% who achieved kkm (75) while there were 31 students with a percentage of 81.58% with learning results below kkm (75), the second cycle showed that only 11 students 28.98% who did not reach the kkm (75) while 27 students with a percentage of 71.05% had achieved the kkm (75), based on the results of cycles 1 and 2 it was found that in cycle 2 the students had achieved classical completion. The results of this research show that the application of the project based learning model with the help of video and power point media can improve student learning outcomes in class V thematic learning at SDN Tolitoli. Keywords: Project-Based Learning, Learning Outcomes, Thematic Learning.